Exploration of the Trade-off between Short Term (Battery) and Long Term (Hydrogen) Storage for a Wind Powered Energy Community - Domene-Fernández, Silvia; Martín-Rivas, Sebastián (IEEE, 2024)
As the share of renewable generation increases in energy communities arises the question of whether total cost (investment + operation) could be minimized by a proper combination of short term (battery) and long term (hydrogen) storage. Here we focus the study on a wind powered energy community with battery storage, grid connection (consumption/injection), and hydrogen (generation, storage and back to power). The main factors that impact the optimal operation and configuration, with particular focus on short and long-term storage, are identified for a general system. A sensitivity analysis is performed on those factors using two-stage optimization problems in a case study with 480 users to numerically quantity their interaction and influence on the solutions.
Keywords: Recursos energéticos renovables; Energía eólica; Wind power generation; Hydrogen storage; Batteries; Energy community